"The Will to Live and the Meaning of Life": Hunger as Vulnerability in French Existential Phenomenology. Issue 49 (3rd July 2018) - Murphy, Ann V.
ABSTRACT: This essay explores the phenomenology of hunger in reference to work by Jean-Paul Sartre, Maurice Merleau-Ponty and Simone de Beauvoir. Considering the wealth of references to hunger in phenomenological literature, very little has been written that acknowledges the importance of hunger in French existential phenomenology in particular. With reference to work by the above authors, this essay examines how hunger alters one's basic experience of space and time, no less one's sense of social belonging. Phenomenology illuminates dimensions of the human experience of hunger that remain veiled in other discourses, and it is vital that efforts to understand hunger engage the profound narratives of disorientation, illness and shame that come to the fore in this body of work.